2005
DOI: 10.1089/end.2005.19.353
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laparoscopy in Management of Renal Stones: Single-Center Experience and Review of Literature

Abstract: Laparoscopic surgery is effective for complex renal stones and allows for adjunctive procedures. It can also be an alternative to percutaneous nephrolithotomy. It complements other minimally invasive procedures, and a need for open stone surgery should be rare in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 32 publications
2
49
0
4
Order By: Relevance
“…Jagdish Chander et al [12] reported a mean age of 33.74 years (18-60 yrs) in the group used in their study. Thiagarajan Nambarajan et al [13] reported a mean age of 51 yr in their study.…”
Section: Discussionmentioning
confidence: 77%
“…Jagdish Chander et al [12] reported a mean age of 33.74 years (18-60 yrs) in the group used in their study. Thiagarajan Nambarajan et al [13] reported a mean age of 51 yr in their study.…”
Section: Discussionmentioning
confidence: 77%
“…Birçok çalışmayla etkinliği gösterilmiş, taşsızlık oranı %71-100 ve açığa dönüş oranı %0-27 arasında bildirilmiştir (11)(12)(13). Gaur'un retroperitoneal boşlukta balon dilatasyonunu bulması ürolojik laparoskopinin gelişmesine büyük katkıda bulunmuştur (14 enfekte idrarın peritoneal boşluk ve organlarla teması gibi bir riski mevcuttur.…”
Section: Böbrek Taşlarıunclassified
“…Gaur'un retroperitoneal boşlukta balon dilatasyonunu bulması ürolojik laparoskopinin gelişmesine büyük katkıda bulunmuştur (14 enfekte idrarın peritoneal boşluk ve organlarla teması gibi bir riski mevcuttur. Buna karşın transabdominal yolla yapılan girişimlerde herhangi bir önemli komplikasyon gelişmediği-ni bildiren çalışmalar da mevcuttur (15,16). Transperitoneal yaklaşımla barsak motilitesinin geç kazanıldığı, analjezik ihtiyacının, ileus ve hastanede kalış sürelerinin daha fazla olduğu gösterilmiştir (17).…”
Section: Böbrek Taşlarıunclassified
“…Laparoscopic surgery has been successfully introduced in the treatment of urinary tract stone disease, with major applications for ureteral calculli and treatment of Ureteropelvic junction (UPJ) anomaly or caliceal diverticula (55,56).…”
Section: Urologic Laparoscopy Drainagementioning
confidence: 99%